The Role of Diet Therapy in Reducing the Cardiovascular Disease Risk in a Patient with a Long-Standing and Recurring History of Obesity - L, Rangelova; M, Nikolova (Journal of Community Medicine and Health Solutions, 2024)
Insulin resistance, often referred to as impaired insulin sensitivity. This clinical case focusses on a woman with insulin resistance and a long-standing and recurring history of obesity to demonstrate how diet therapy can be applied in addition to standard medication therapy.